Machining Process Simulation to Find NC Program and Cutting Time - Haris Nasution, Abdul; Napid, Suhardi; Sri Poneni, Istu; Hasibuan, Abdurrozzaq; ., Suliawati (International Journal of Engineering and Technology, 2018)
To produce the bulk products in metal industry, tool path and cutting time are necessary to predict the amount of product that can be produced within a certain time (throughout the tool life). The ways used so far are to sacrifice some of the product as an experimental material. Using such a method will cause many losses, including much time to machining product by trial and error will cause the waste materials. To solve problem above, this paper described solution to get the accuracy of tool path and cutting time. The solution offered is to use software to simulate the machining process, so that losses due to time and wasted materials can be resolved.